Konsep dan Teori Manajemen Pendidikan Sekolah Tingkat Kalangan Atas dan Kalangan Bawah - Imam Ma’arif (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to analyze the application of school management theory to two categories of schools, namely schools that serve the upper class and schools that serve the lower class. This study uses a qualitative descriptive approach with data collection techniques through interviews, observations, and documentation studies. The results of the study show that upper-class schools apply Classical Administrative Theory and Transformational Leadership Theory with a focus on resource optimization and innovation to achieve high educational standards. In contrast, lower-class schools face resource constraints and apply Contingency Theory and Systems Theory, which allow them to adapt and find creative solutions to meet students' needs. The conclusion of this study highlights significant differences in management approaches in both types of schools, which are greatly influenced by socio-economic factors and resource availability. The education policy recommendations emphasize the importance of ongoing support for lower-class schools so that they can improve the quality of education and reduce the educational gap between the two groups.